E o Instituto Federal integra a jornada: potencialidades emancipatórias nas trajetórias de jovens egressos do curso técnico em Química integrado ao ensino médio em Institutos Federais no Centro-Oeste brasileiro - Chagas, Selton Evaristo de Almeida (2020)
This thesis aimed at investigating the emancipatory potential developed by students graduated in the Technical Course in Chemistry Integrated to High School of three campi of Federal Institutes (IFs) of the Brazilian Midwest (Aparecida de Goiânia and Inhumas campi of the Federal Institute of Goiás, and Rondonópolis campus of the Federal Institute of Mato Grosso). The objective was to analyze how the experiences lived in Integrated High School, considering the peculiarities of these educational institutions, turned into emancipatory potentialities in the students' journey, from the hypothesis that the Integrated High School of the IFs allows students to undergo experiences that trigger the expansion of their political participation and the construction of academic and professional life itineraries in contradiction to the immediate demands of the market, constituting themselves as emancipatory potentialities for them and for social groups to which they feel part of. The category "emancipatory potentialities" was forged from studies on human and political emancipation and the history of technical and technological education in Brazil, based on readings of Marxist-based historical-critical pedagogy and the sociology of education development by Pierre Bourdieu. The results of the field research also corroborated the constitution of this category of analysis, as well as its use as a tool to explain reality. Secondary data were collected from the School Registration Secretariats of the surveyed campi and at the Nilo Peçanha Platform, in order to outline a sociographic profile of Integrated High School students throughout the decade of 2010. For the empirical research, all students who graduated in 2016 from this course in the three schools were contacted, it was conducted a survey with those who consented, and in-depth interviews with a portion of this group. In order to understand how the IFs developed as mediation in their unique trajectories, it was used an applied way of a sociological portrait as a technique for the orientation and analysis of the interviews, adding to it contributions from Marxism and Sociology of Pierre Bourdieu. Experiences of different natures at the IFs, such as internship, research, extension, contact with sports, arts and knowledge of the Human Sciences corroborated a wide acquisition of objectifications and subjectivities of the human race to these young people from the popular classes, and, consequently, the development of their individualities. Three types of emancipatory potentials were categorized, which include dispositions in development from the early childhood of the interviewees, which intertwined with their class origins and strategies developed by their families during their schooling projects. It was concluded that the potential for social transformation is restricted to an individualist project of the subject, dissociated from a class or group project, linking it in part to a concept of hegemonic emancipation disseminated by international and multilateral agents of capital. Empirically analyzing the perspective of emancipation developed through the school and institutional practices of these schools encompasses understanding the contradictions inherent in the process, such as the recognition of limiting conditions, and the concrete possibilities of expanding this “extraordinary gain” in terms of Brazilian public education, especially for students from the most vulnerable classes.